1ISG-018 Organisational commitment of hospital pharmacists, relating to the supportive organisational environment. (March 2019) - Ahn, M; Jeong, H
Abstract : Background: As hospital pharmacists have expanded their role from simple drug dispensing to patient-oriented clinical practice, they have augmented their professionalism (the attitudes and belief as professional (PF)) as hospital pharmacists. Thus it has been important to make them commit to hospital organisation. Purpose: This study examines how a supportive organisational environment (SOE) influences organisational commitment (the attitudes and behaviours to devote themselves to their organisation (OC)) of hospital pharmacists in South Korea. In particular, we have analysed the role of professionalism in the relationship. Material and methods: This study included 224 Korean hospital pharmacists, who responded to our survey from August to September 2017. The components having an eigenvalue greater than 1 were attained from the factor analyses for PF, OC and SOE. The effect of each factor of SOE was evaluated by regression analysis, while the mediation effect of PF was ascertained by mediation analysis. Results: Factor analysis (over 0.7 of Cronbach's α) showed that the PF of hospital pharmacists was determined by a 'professional organisation as a major referent (0.722)', 'mission in public service (0.851)' and 'autonomy (0.726)'. The OC of hospital pharmacists to a hospital organisation was decided by the fourth dimensional perspective that comprises 'affective OC (to identify with organisation effectively, 0.861)', 'continuance benefit OC (to commit increased benefits as a result of tenure, 0.759)' and 'normative OC (to commit because it is morally right, 0.741)'. The SOE was determined by 'organisational support (0.870)', 'educational support (0.918)', 'supervisory support (0.908)' and 'colleague support (0.921)'. The result of regression analysis substantiated that organisational support influences affective OC (p<0.001) and supervisor support effects both affective (p<0.01) and normative (p<0.05) OC. It was confirmed that PF concurrently effects affective (p<0.001) and normative (p<0.001) OC as well as the mediation effect that reinforces organisational commitment (p<0.05). Conclusion: The higher the PF, the stronger the OC by hospital pharmacists. Thus, respecting autonomy, reflecting the opinions and providing welfare are necessary in strengthening pharmacist's professionalism. Besides, supervisors should have an interest in the job performance, present distinct goals of hospital pharmacists and help them exert their professionalism. Furthermore, hospital pharmacists' performances should promote public service. References and/or acknowledgements: I would like to express my gratitude to many hospital pharmacists that responded to our survey questionnaire in their busy schedule. No conflict of interest.